Comparison of the Clinical Outcomes of Plastering and Bandage Treatment Methods in Patients With Ankle Sprains: A Randomized Clinical Trial Study - Kamran Asadi; Masoud Fallah Khosh Ghalb; Khashayar Cyrus (مجله دانشگاه علوم پزشکی گیلان)
Background Treatment measures for ankle sprains include care recommendations, symptomatic therapy, joint immobilization using bandages and plasters, and reconstructive surgery. Objective The purpose of this study is to compare the therapeutic effect of bandages and plastering in the treatment of ankle sprain. Methods This study was a randomized clinical trial that was conducted on 78 patients who were referred to the Poursina Hospital emergency room with ankle sprains. Patients who needed treatment after being diagnosed with ankle sprain were included in the study. The patients who met the inclusion criteria were divided into two groups A (plaster) and B (bandage) by a simple random method, and 3, 6, and 12 weeks after the start of the treatment, they were examined for the level of pain. Results The results showed that the amount of pain based on the visual analogue scale (VAS) after three and six weeks in the bandage group was lower than in the plaster group and this difference was statistically significant (P<0.001). Ankle-hindfoot scale (AHS) after 3, 6, and 12 weeks had the same average in the two studied groups. The duration of activity restriction in the plaster group was significantly lower than in the bandage group. The treatment results were evaluated in terms of complete recovery, time to return to work and activity, and pain level. Conclusion Plastering treatment reduces the days of activity limitation and patients return to work and daily activities faster. However, plastering has limitations, such as more cost and limiting the movements of the limbs. For a logical conclusion, there is a need for more studies considering all aspects of applying bandage and plastering methods in ankle sprain.